A Facile Route for the Preparation of Monodisperse Iron nitride at Silica Core/shell Nanostructures - Kim, Hoonsub; Im, Pyung Won; Piao, Yuanzhe (Frontiers in Bioengineering and Biotechnology, 2021)
Uniform-sized iron oxide nanoparticles obtained from the solution phase thermal decomposition of the iron-oleate complex were encapsulated inside the silica shell by the reverse microemulsion technique, and then thermal treatment under NH3 to transfer the iron oxide to iron nitride. The transmission electron microscopy images distinctly demonstrated that the as-prepared iron nitride@silica core/shell nanostructures were highly uniform in particle-size distribution. By using iron oxide nanoparticles of 6.1 nm, 10.3 nm, 16.2 nm, and 21.8 nm as starting materials, iron nitride nanoparticles with average diameters of 5.6 nm, 9.3 nm, 11.6 nm, and 16.7 nm were produced, respectively. The acid-resistant properties of the iron nitride@silica core/shell nanostructures were found to be much higher than the starting iron oxide@silica. A superconducting quantum interference device was used for the magnetic characterization of the nanostructure. Besides, magnetic resonance imaging (MRI) studies using iron nitride@silica nanocomposites as contrast agents demonstrated T2 enhanced effects that were dependent on the concentration. These core/shell nanostructures have enormous potential in magnetic nanodevice and biomedical applications. The current process is expected to be easy for large-scale and transfer other metal oxide nanoparticles.